Lateral Thinking Among Secondary School Students - العبودي, حلا علي حسين (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The current research problem includes the following questions: 1- Do middle school students possess lateral thinking? 2- Are there statistically significant differences among middle school students based on the following variables: gender (males - females) and specialization (scientific - literary)? Research objectives: 1. To identify lateral thinking among middle school students (fourth and fifth grades). 2. To identify statistically significant differences in lateral thinking according to gender (males - females) and specialization (scientific - literary). Research Methodology: The researcher used the descriptive approach as it was most appropriate for the research sample. The research sample community of middle school students in Najaf Governorate was (22505) male and female students from both levels, the number of the fourth grade of them was (15762), the number of the scientific grade of them was (14468), the number of males was (10499), and the number of females was (3969). As for the literary grade, it was (1294), the number of males was (706), the number of females was (588), and the number of the fifth grade of them was (6743), the number of scientific grade of them was (5801), the number of males was (2432), while the number of females was (3369). As for the literary branch, their total was (942), the number of males was (481), and the number of females was (461). The basic research sample was selected using a stratified random method. To achieve the research objectives, the researcher built a lateral thinking scale. Statistical analysis indicators such as validity and reliability were verified. The number of lateral thinking items was (30). Thus, the lowest score obtained by the respondent was (30), and the highest score obtained by the respondent was (150). The hypothetical average score for the lateral thinking scale was (90). The higher the respondent obtained on this scale, the more he/she possesses lateral thinking. The results of the current study are as follows: 1. Middle school students exhibit lateral thinking. 2. There are statistically significant differences in lateral thinking according to the gender variable, in favor of females. 3. There are statistically significant differences in lateral thinking according to the branch variable, with the scientific branch being the preferred branch.